Finite Element Modeling of Five Phase Permanent Magnet BLDC Motor for High Power Density Application - Kiran George; Shinoy K.S.; Sija Gopinathan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
Fault-tolerant capability of electrical motor drives is an essential feature in applications such as automotive, aeronautic, and many others. A multi-phase permanent-magnet BLDC motor exhibits a high fault tolerant capability hence increasing the reliability, as it can be designed to reduce the fault occurrence as well as to operate indefinitely in the presence of fault. With multi independent phases, in the event of failure of one or more, the remaining healthy phases let the motor to operate properly. This paper presents finite element modeling and results of a five-phase permanent magnet brushless motor designed for high power density application.DOI: http://dx.doi.org/10.11591/ijpeds.v3i4.4184